Formulasi Strategi Korporasi pada Industri Pengolahan Pangan - Aurellia, Azarine Faustina; Shafira, Alvinia; Nurrizki, Diza; Wiratmadja, Iwan Inrawan (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2024)
MSME X is one of the tofu producers in Sentra Industri Tahu Cibuntu, Kel. Babakan, Kec. Babakan Ciparay, Bandung City 40222 and founded in 1999. The variety of products are silk tofu, milk tofu, cheese tofu, and chili tofu. MSME X is the pioneer of silk tofu and milk tofu in Indonesia. Currently, tofu products are marketed to dozens of vegetable and tofu seller in the West Java. This research aims to formulate effective corporate strategy proposals that can support the development of MSME X. The methods used in determining the formulation of corporate strategies are environmental scanning, TOWS analysis, Internal Factor Evaluation (IFE) Matrix and External Factor Evaluation (EFE) Matrix, competitive position analysis mapping, portfolio TOWS matrix, and Quantitative Strategic Planning Matrix (QSPM). Based on the analysis, the priority alternative strategies for MSME X are product and technology development strategies and market penetration strategies. Product and technology development strategies can be carried out by product development, technology investment, and expanding product lines, while market penetration strategies can be carried out by increasing brand awareness, expanding distribution networks, conducting digital marketing, increasing offline sales channels, and improving customer service.